2023
DOI: 10.1002/bse.3520
|View full text |Cite
|
Sign up to set email alerts
|

Two interventions for mitigating the harms of greenwashing on consumer perceptions

Abstract: Growing demand for environmentally friendly products has led to an increase in companies exaggerating their environmental credentials, a practice commonly referred to as “greenwashing.” To identify the impact of greenwashing and to test potential interventions, we designed an online experiment featuring a series of three advertisements featuring hypothetical companies. A representative sample of 2352 participants were randomised into a control group or one of two intervention groups. Intervention groups saw ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…They identified that the probability of classifying a product as bio or non-bio was higher when these product cues fitted the expected status of the product. Dutta-Powell et al (2023) also looked at how literacy or prebunking interventions, could enable customers to identify common greenwashing strategies. Some of these strategies could be popularized among consumers, through advocacy and pressure groups, to minimize consumers falling prey to greenwashing strategies.…”
Section: Theoretical Implications and Discussionmentioning
confidence: 99%
“…They identified that the probability of classifying a product as bio or non-bio was higher when these product cues fitted the expected status of the product. Dutta-Powell et al (2023) also looked at how literacy or prebunking interventions, could enable customers to identify common greenwashing strategies. Some of these strategies could be popularized among consumers, through advocacy and pressure groups, to minimize consumers falling prey to greenwashing strategies.…”
Section: Theoretical Implications and Discussionmentioning
confidence: 99%